Effect of Probiotic Curd on Salivary pH and Streptococcus mutans: A Double Blind Parallel Randomized Controlled Trial - Srivastava, Shivangi (J Clin Diagn Res, 2016)
BACKGROUND: Dairy products like curd seem to be the most natural way to ingest probiotics which can reduce Streptococcus mutans level and also increase salivary pH thereby reducing the dental caries risk. OBJECTIVES: To estimate the role of probiotic curd on salivary pH and Streptococcus mutans count, over a period of 7 days. MATERIALS AND METHODS: This double blind parallel randomized clinical trial was conducted at the institution with 60 caries free volunteers belonging to the age group of 20-25 years who were randomly allocated into two groups. Test Group consisted of 30 subjects who consumed 100ml of probiotic curd daily for seven days while an equal numbered Control Group were given 100ml of regular curd for seven days. Saliva samples were assessed at baseline, after ½ hour 1 hour and 7 days of intervention period using pH meter and Mitis Salivarius Bacitracin agar to estimate salivary pH and S. mutans count. Data was statistically analysed using Paired and Unpaired t-test. RESULTS: The study revealed a reduction in salivary pH after ½ hour and 1 hour in both the groups. However after 7 days, normal curd showed a statistically significant (p< 0.05) reduction in salivary pH while probiotic curd showed a statistically significant (p< 0.05) increase in salivary pH. Similarly with regard to S. mutans colony counts probiotic curd showed statistically significant reduction (p< 0.05) as compared to normal curd. CONCLUSION: Short-term consumption of probiotic curds showed marked salivary pH elevation and reduction of salivary S. mutans counts and thus can be exploited for the prevention of enamel demineralization as a long-term remedy keeping in mind its cost effectiveness.